2022
DOI: 10.1155/2022/8552142
|View full text |Cite
|
Sign up to set email alerts
|

A Neighborhood Grid Clustering Algorithm for Solving Localization Problem in WSN Using Genetic Algorithm

Abstract: Finding the location of sensors in wireless sensor networks (WSNs) is a major test, particularly in a wide region. A salient clustering approach is laid out to achieve better performance in such a network using an evolutional algorithm. This paper developed a clustered network called neighborhood grid cluster which has a node assuming the part of a cluster center focused in every grid. Grid-based clustering is less difficult and possesses a lot of benefits compared to other clustering techniques. Besides, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some of these studies are summarized as shown in Table VI. The [115], [116] proposed a clustering method called Neighborhood Grid Cluster (NGC) to address the localization of WSNs nodes challenges and reduce energy consumption. The NGC approach utilizes the GA optimization process to improve the efficiency and reliability of localization algorithms (to estimate the target node's position).…”
Section: A Evolutionary Algorithmsmentioning
confidence: 99%
“…Some of these studies are summarized as shown in Table VI. The [115], [116] proposed a clustering method called Neighborhood Grid Cluster (NGC) to address the localization of WSNs nodes challenges and reduce energy consumption. The NGC approach utilizes the GA optimization process to improve the efficiency and reliability of localization algorithms (to estimate the target node's position).…”
Section: A Evolutionary Algorithmsmentioning
confidence: 99%
“…In [33], data aggregation and clustering-based methods are presented to improve the lifetime of the network based on the node localization and routing mechanism. In [34], a grid clustering method is presented to identify sensor node locations based on the genetic algorithm. In [35], a detailed review is performed to analyze localization problems and their performance.…”
Section: Literature Surveymentioning
confidence: 99%
“…To the best of our knowledge, existing grid clustering algorithms work by dealing with nodes and cells. The former mainly includes FDGB [ 21 ] and GCBD [ 22 ], while the latter mainly includes GBCN [ 23 ], GCDPP [ 24 ], NGCGAL [ 25 ], and CMSPGD [ 26 ]. However, different grid-based clustering methods have their own considerations in grid space, node or cell processing, and cluster generation strategies, resulting in differences in clustering performance.…”
Section: Related Workmentioning
confidence: 99%